Blogging and RSS : a librarian's guide - Sauers, Michael P. (Information Today, 2006)
Libraries increasingly use blogs and RSS feeds to reach out to users, while librarians blog daily on a range of personal and professional topics. The way has been paved by the tech-savvy and resource-rich, but any library or librarian can successfully create and syndicate a blog today. Sauers showcases interesting and useful blogs, shares insights from librarian bloggers, and offers step-by-step instructions for creating, publishing, and syndicating a blog using free Web-based services, software, RSS feeds, and aggregators.